2019
DOI: 10.1029/2019jb018285
|View full text |Cite
|
Sign up to set email alerts
|

Separating Sea and Slow Slip Signals on the Seafloor

Abstract: Seafloor pressure measurements hold promise for estimating vertical displacements from transient slow slip events on submarine faults. We assess the accuracy of pressure offset estimates that evolve over days to weeks and the confidence with which they may be attributed to tectonic deformation or to the ocean water column. One common approach to resolve this ambiguity assumes water column pressures vary insignificantly over the study region and are represented by stable reference site pressures. Assessing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 29 publications
4
25
0
Order By: Relevance
“…The ROMS model reasonably well predicts the first-order features of the nontidal seafloor pressure field, as evidenced in comparisons between a variety of predicted and observed data found in Hadfield et al (2007) and between seafloor predicted and observed pressures recorded during the HOBITSS experiment and low-pass filtered with a corner of 0.5 days −1 (Gomberg et al, 2020). The latter verifies the minimal contribution of the tides with periods longer than several days noted above.…”
Section: 1029/2020gl087273supporting
confidence: 68%
See 1 more Smart Citation
“…The ROMS model reasonably well predicts the first-order features of the nontidal seafloor pressure field, as evidenced in comparisons between a variety of predicted and observed data found in Hadfield et al (2007) and between seafloor predicted and observed pressures recorded during the HOBITSS experiment and low-pass filtered with a corner of 0.5 days −1 (Gomberg et al, 2020). The latter verifies the minimal contribution of the tides with periods longer than several days noted above.…”
Section: 1029/2020gl087273supporting
confidence: 68%
“…However, the latter have advantages relative to recorded pressures that include their long durations, an absence of instrumental and localized environmental noise, and importantly contain only the posited causal ocean pressures and not those that may exist due to seafloor deformation from the SSEs. Comparisons between the simulated and observed seafloor pressures are described in Gomberg et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, He et al (2018) yielded moderate improvement by using deep current measurements and the geostrophic balance assumption to remove the ocean circulation contribution. Gomberg et al (2019) suggested an approach to reduce the water column and some instrumental noise based on correlations between seafloor temperature and pressure changes. In this paper, we did not apply the machine learning method to these corrected measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used OBP observations to identify specific slow slips (Ohta et al, 2012;Ito et al, 2013;Wallace et al, 2016). Recent efforts to improve sensitivities to find transient/ramp steps in OBP records have been increasingly made using ocean models, statistical methods, and/or machine learning in these regions (Hino et al, 2014;Gomberg et al, 2019;Muramoto et al, 2019;He et al, 2020).…”
Section: Detectability Of Seafloor Deformation and Further Root-mean-square Reductionmentioning
confidence: 99%
“…Tidal signals have been precisely estimated by observed records or numerical predictions (Tamura et al, 1991;Egbert and Erofeeva, 2002). Lowerfrequency, non-tidal oceanic variations can be estimated by numerical ocean models, but their accuracy is not typically sufficient for detection of slow slips of less than a few centimeters in OBP observations (Fredrickson et al, 2019;Gomberg et al, 2019;Muramoto et al, 2019). Nevertheless, this approach of reducing ambient oceanic noises is fundamental, and is suitably applied for both multiple-station and single-station observations.…”
Section: Introductionmentioning
confidence: 99%